The invasion of a mustard seed a reading of Mark 5.1-20 - Garroway, Joshua D. (2009)
This article reads Mark's tale of the Gerasene demoniac as a narrative explication of the parables in the preceding chapter - particularly the mustard seed - in which the kingdom of God is described in light of the paradigmatic kingdom of the period, imperial Rome. The account portrays the violent destruction of Rome, achieved through synecdoche by the annihilation of an occupying "Legion", as well as the peaceful infiltration of an new kingdom, achieved through mimesis in the second scene by the demoniac's "invasion" of a hostile crowd. In so doing, the passage both mimics and subverts standard ancient ideologies of kingdom and invasion.
Keywords: Die Heilung des Besessenen von Gerasa; Gleichnis; Reich Gottes; Postkolonialismus